Rancang Bangun dan Pengujian Kinerja Mesin Pemisah Isi Biji Buah Durian - Akmal Indra (Politeknik Negeri Jakarta, 2020)
The making process of Lempuk Durian is almost same as Dodol’s, the difference is only at the mixing of sticky rice (ketan). Dodol is made with the mixing of sticky rice while Lempuk isn’t. Durian flesh is separated by its contents and then finely ground with a grinding machine. The process of separating the contents and seeds of durian fruit is still using conventional methods, by using a punch-filled basket while being pressed by hand. This way can cause injury to the hand, this way can cause injury to the hand, requires a long time and workers get tired more quickly. The purpose of this research is to make content and durian seed separator machines and conduct performance analysis. This content and durian seed separator machine has a capacity of 20kg / production. After testing and observing the durian seed separator machine, then the performance analysis is carried out to determine the ability of the machine. Machine working capacity (KKM) is obtained at 1 kg / minute with the value of the separation of contents and durian seeds of 87%.